Neuromodulation by means of phase-locked auditory stimulation affects key marker of excitability and connectivity during sleep. Issue 1 (10th August 2021) - Sousouri, Georgia; Krugliakova, Elena; Skorucak, Jelena; Leach, Sven; Snipes, Sophia; Ferster, Maria Laura; Da Poian, Giulia; Karlen, Walter; Huber, Reto
Abstract: The propagating pattern of sleep slow waves (high-amplitude oscillations < 4.5 Hz) serves as a blueprint of cortical excitability and brain connectivity. Phase-locked auditory stimulation is a promising tool for the modulation of ongoing brain activity during sleep; however, its underlying mechanisms remain unknown. Here, eighteen healthy young adults were measured with high-density electroencephalography in three experimental conditions; one with no stimulation, one with up- and one with down-phase stimulation; ten participants were included in the analysis. We show that up-phase auditory stimulation on a right prefrontal area locally enhances cortical involvement and promotes traveling by increasing the propagating distance and duration of targeted small-amplitude waves. On the contrary, down-phase stimulation proves more efficient at perturbing large-amplitude waves and interferes with ongoing traveling by disengaging cortical regions and interrupting high synchronicity in the target area as indicated by increased traveling speed. These results point out different underlying mechanisms mediating the effects of up- and down-phase stimulation and highlight the strength of traveling wave analysis as a sensitive and informative method for the study of connectivity and cortical excitability alterations.